Modeling and Simulation of Vibrations in Turning Using Matlab to Analyse Stability of the Cutting Process - محمد محمد خير; ناصر اماني (Latakia University Journal -Engineering Sciences Series, 2021)
The study has been carried out during the year 2020 in Tishreen University. Modeling and simulation has been done for dynamic state of tool - workpiece system in turning, based on the mathematical model of system, where the mathematical model used is a linear model. In the beginning, the differential equations that describe the vibration between the workpiece and the cutting tool have been mathematically concluded, then modeling and simulation operations for specific parameters have been applied for the mathematical model using Matlab, so we can make sure if the system is stable or unstable, which affect directly on the quality of workpiece.